CONSECUTIVE INTERPRETER TRAINING IN A NON-STANDARD ENVIRONMENT: AN AUTONOMOUS APPROACH - Barakat, Eman Mohammed Mohammed Ahmed (International Journal of Language Academy, 2019)
Conducting interpreter training in a non-standard environment characterized by limited training courses, large groups of students, insufficient class time and overloaded instructors prevents from achieving progress in interpreting performance and negatively affects training outcomes. Against this context, the present paper describes a student-centered training approach where students are trained to develop their interpreting skills and assess their own performance for the purpose overcoming training constraints, fostering learner autonomy and creating life-long learners. The sample of the study consisted of 21 translation students receiving consecutive interpreter training at UST (University of Science and Technology, Yemen). They were asked to rate their recorded interpreting performance using assessment criteria that covers three categories: content, language and delivery. Students were also asked to write their positive and negative reflections on this mode of assessment. Furthermore, an online survey was conducted to find out students’ perceptions on self-assessment. The correlation between students’ self-assigned grades and teachers’ assessment was also calculated. Findings suggested a positive attitude towards self-assessment among interpreter students as it served to identify areas of strengths and weaknesses. Students reflections also provided useful suggestions for instructors on applying self-assessment more efficiently. It was also found that the students and teachers’ assessments were close which meant that students were in a position to be in charge of their own learning.
Keywords: Consecutive Interpreting; Non-Standard Training Environment; Self-Assessment; Assessment Criteria.; Learner Autonomy